A peregrinação ao sagrado: os caminhos que levam à Romaria/MG - Marques, Luana Moreira (2017)
Pilgrimages are a way of approaching the materialization of the sacred in different religions and destinations. Such destinations, when collectively recognized, are understood as sacred places. Many subjects get on the road to reach them. In the journey, they modify spaces, landscapes, daily life, and also transform themselves, engaging in a web of relationships, practices, places and people that is (re)constructed all the time. Considering the importance of the sacred place for the study of religiosity, the present study focuses on uncovering why and how the sacredness of a place occurs, observing the way in which this process changes the space and the daily lives of multiple subjects. It has as a case study the municipality of Romaria-MG, where the devotion to Our Lady of the Abbey modifies practices and landscapes, mainly in the periods of pilgrimage and celebration. The thesis starts from the analysis of the sacred place, passing through the importance and the characteristics of the pilgrimages over time and space. Afterwards, it goes on to the case of the devotion of Our Lady of the Abbey, who pilgrims along with her devotees to Brazil, establishing herself in Romaria- MG, among other destinations. The pilgrimage of this sacred symbol propels the displacement of several subjects who obtain on their path social, cultural, and spiritual nourishment, and even physical nourishment for their desires and needs. Once at the destination, during the celebration of the patroness, different types of socio-spatial relationships are conjugated, coming from the intense convergence of flows of multiple subjects laden with different motivations, which turns Romaria into a stage of rich and complex encounters, conflicts and exchanges. The research was developed based on bibliographical reviews, documentary analysis, as well as the collection of data and information during fieldwork comprised in the period between 2011 and 2017. Throughout the text it is possible to follow the genesis and development of the municipality of Romaria and its constitution as a sacred place, as well as reflect on the reasons for the sacredness of other spaces.